Modified Value-Based Adoption Model (VAM) in Paid Entertainment Mobile Apps in Yogyakarta - Lusia Tria Hatmanti Hutami; Bernadetta Diansepti Maharani (Politeknik Negeri Bengkalis, 2022)
After the outbreak of COVID-19, there was an increase in the download of mobile applications because at that time there were regulations that required people to stay at home and maintain social distance. This has made changes to the lifestyle of consumers, some of them are no longer satisfied using the application alone but voluntarily pay to enjoy more offers in the application. We used a modified VAM to explain the intention of adoption through a benefit-sacrifice approach. Therefore, the purpose of this study is to determine the factors that influence adoption intention through the perceived value. This research uses path analysis method on 100 paid mobile entertainment application users in Yogyakarta. The results indicate that the enjoyment and perceived fee are proven to affect the perceived value and the perceived value has a significant effect on the intention of consumer adoption in the use of paid mobile applications.After the outbreak of COVID-19, there was an increase in the download of mobile applications because at that time there were regulations that required people to stay at home and maintain social distance. This has made changes to the lifestyle of consumers, some of them are no longer satisfied using the application alone but voluntarily pay to enjoy more offers in the application. We used a modified VAM to explain the intention of adoption through a benefit-sacrifice approach. Therefore, the purpose of this study is to determine the factors that influence adoption intention through the perceived value. This research uses path analysis method on 100 paid mobile entertainment application users in Yogyakarta. The results indicate that the enjoyment and perceived fee are proven to affect the perceived value and the perceived value has a significant effect on the intention of consumer adoption in the use of paid mobile applications.